The impact of individual relationships on performance and reformation of R&D alliances - Alba Sanchez-Navas; Xavier Ferras-Hernandez (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: To examine how trust, conflict, commitment and communication affect R&D alliance performance, the individual's satisfaction with the alliance and their intention to collaborate with the same partners in the future. Design/methodology/approach: Empirical research Findings: Trust, conflict, commitment and communication are positively related to alliance performance, although trust and communication are the characteristics with the strongest fit. In addition, successful alliances influence positively on individual satisfaction and raise the willingness to reform the alliance with the existing alliance members. Originality/value: This study has enriched current understanding of the relationship among individual relations, alliance performance and reformation in R&D alliances.
Keywords: 650; R&D alliances; performance; individual relations; reformation; satisfaction; trust; conflict; commitment; communication